Pesantren-Based Character Education Model for Strengthening Students’ Moral Competence in Malaysia - Rusli Wan (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
The increasing prevalence of moral decline, behavioral misconduct, social intolerance, cyberbullying, and weakening ethical awareness among students has intensified the importance of character education within contemporary educational systems. In Malaysia, educational institutions increasingly recognize the need to strengthen students’ moral competence through value-based and holistic educational approaches. The pesantren-based character education model, rooted in Islamic boarding school traditions emphasizing discipline, spirituality, moral habituation, and communal learning, offers a promising framework for cultivating students’ ethical awareness and moral behavior. This study explores the role of a pesantren-based character education model in strengthening students’ moral competence in Malaysia and examines its potential contribution within Islamic educational settings. Using a qualitative literature review approach, the study analyzes scholarly publications, educational reports, and theoretical discussions related to character education, moral competence, pesantren traditions, and Islamic education. The findings indicate that pesantren-based education positively contributes to students’ moral competence through the internalization of Islamic values, moral habituation, exemplary leadership (uswah hasanah), spiritual discipline, communal responsibility, and reflective learning. Students exposed to pesantren-inspired educational practices demonstrate stronger moral reasoning, ethical responsibility, empathy, discipline, and prosocial behavior. However, challenges remain, including curriculum adaptation, institutional differences, teacher preparedness, and sociocultural diversity within Malaysian educational contexts. The study concludes that pesantren-based character education may serve as an effective educational model for strengthening students’ moral competence in Malaysia when supported by curriculum integration, educator training, and culturally responsive implementation.